FEATURES OF DAILY BLOOD PRESSURE IN PATIENTS WITH NEPHROGENIC ARTERIAL HYPERTENSION - Sapayeva Z.A.; Jumaniyozov B. K. (Web of Journals Publishing, 2023)
Cardiovascular complications caused by nephrogenic arterial hypertension are the leading cause of death in patients with chronic renal failure. The most significant factor in the pathogenesis of hypertension in diffuse kidney diseases is considered to be sodium retention, accompanied by an increase in the volume of extracellular fluid and cardiac output. The adverse effect of uncontrolled hypertension on renal outcomes has been demonstrated by numerous studies. The data presented in the article indicate that in patients with nephropathies, in order to slow down and prevent the deterioration of kidney function, it is desirable to achieve target blood pressure values. Daily blood pressure monitoring in nephrology makes it possible to determine the severity of hypertension and its daily fluctuations, select adequate antihypertensive treatment, and evaluate its effectiveness.
Keywords: cultural terms, techniques, linguistic nuances, cultural, ethical considerations, cultural gaps